Nilai-Nilai Multikultur di Sekolah Multi Etnik: Studi dalam Pembelajaran Sejarah - Jamin Safi; Suharlin Ode Bau (Universitas Galuh, 2023)
This research examines the strengthening of multicultural values in multi-ethnic schools and the constraints of strengthening multicultural values in learning history in multi-ethnic schools, SMA Negeri 1 Ternate. This research is a qualitative type. Information collection uses interview techniques, field observations, and document analysis. Meanwhile, data validity was carried out using the triangulation technique. Data analysis started with data reduction, data presentation, and conclusion. The study results show that integrating multiculturalism values in history learning can form a sense of togetherness among students so that they can accept and appreciate differences in ethnicity and religion. Multicultural values such as tolerance, mutual respect, unity, mutual respect, cooperation, and mutual help are instilled in students to strengthen unity and oneness among people. The obstacle faced is the inconsistency of students' parents with what teachers have taught at school. Multiculturalism can be a vehicle for increasing the degree of mutual respect between ethnicities, tribes, and religions. Strengthening pluralistic values can strengthen diversity among fellow Indonesian citizens. Multicultural education can educate students about unity and integrity to avoid inter-ethnic, ethnic, and religious conflicts.